Gradual pressure-induced change in the magnetic structure of the noncollinear antiferromagnet Mn3Ge - Sukhanov, A. S.; Singh, Sanjay; Caron, Luana; Hansen, Th; Hoser, A.; Kumar; Borrmann, H.; Fitch, A.; Devi, P.; Manna, Kaustuv; Felser, Claudia; Inosov, D. S. (Physical Review B, 2018)
By means of powder neutron diffraction we investigate changes in the magnetic structure of the coplanar noncollinear antiferromagnet Mn3Ge caused by an application of hydrostatic pressure up to 5 GPa. At ambient conditions the kagomé layers of Mn atoms in Mn3Ge order in a triangular 120-spin structure. Under high pressure the spins acquire a uniform out-of-plane canting, gradually transforming the magnetic texture to a noncoplanar configuration. With increasing pressure the canted structure fully transforms into the collinear ferromagnetic one. We observed that magnetic order is accompanied by a noticeable magnetoelastic effect, namely, spontaneous magnetostriction. The latter induces an in-plane magnetostrain of the hexagonal unit cell at ambient pressure and flips to an out-of-plane strain at high pressures in accordance with the change of the magnetic structure.
CRIS-Team Scopus Importer:2022-04-14